2019
DOI: 10.3349/ymj.2019.60.11.1054
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators and Outcome Measures of Endoscopy in the National Cancer Screening Program

Abstract: Purpose: Quality indicators of the National Endoscopy Quality Improvement Program (NEQIP) and outcome measures of endoscopy in the National Cancer Screening Program (NCSP) in Korea are not clear. We evaluated the quality indicators of the revised NEQIP and outcome measures of endoscopy at different types of healthcare facilities participating in the NCSP. Materials and Methods: This study was conducted between March and August 2018 in primary, secondary, and tertiary healthcare facilities that perform endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…Unfortunately, however, 54.2% of participants in our study did not previously participate in the educational process, only 80.3% of them responded that they worked in accordance with the reprocessing guidelines. Moreover, previous studies conducting in NSCP have shown that 15-17% of physicians did not follow the reprocessing guidelines [18], and only 53.3% of nursing staff completed the reprocessing training program [11]. Therefore, based on the above ndings, we argue that endoscope reprocessing training should be conducted more actively to achieve better performance of endoscopy infection control throughout the country.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Unfortunately, however, 54.2% of participants in our study did not previously participate in the educational process, only 80.3% of them responded that they worked in accordance with the reprocessing guidelines. Moreover, previous studies conducting in NSCP have shown that 15-17% of physicians did not follow the reprocessing guidelines [18], and only 53.3% of nursing staff completed the reprocessing training program [11]. Therefore, based on the above ndings, we argue that endoscope reprocessing training should be conducted more actively to achieve better performance of endoscopy infection control throughout the country.…”
Section: Discussionmentioning
confidence: 79%
“…In Korea, the Korean Society of Gastrointestinal Endoscopy (KSGE) presented the rst endoscope reprocessing guidelines in 1995 and recently revised and published the third endoscope reprocessing guideline in 2015 [10]. Additionally, the National Endoscopy Quality Improvement Program included endoscope reprocessing to enhance the endoscopy unit quality by performing national cancer screening, which was introduced and revised in 2009 [10,11]; the Accredited Endoscopy Unit Program has recently been updated [12].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies conducted on the NSCP have shown that 15-17% of physicians did not follow the reprocessing guidelines, 23 and only 53.3% of nursing staff completed the reprocessing training program. 15 Based on the above findings, more than half of the workers in the endoscopy unit did not receive sufficient reprocessing training, although the training affected actual practice. Thus, adequate training should be provided to endoscopy workers to achieve better infection control related to endoscopic procedures throughout the country.…”
Section: Discussionmentioning
confidence: 97%
“…14 Additionally, the National Endoscopy Quality Improvement Program, introduced and revised in 2009, included endoscope reprocessing to enhance the endoscopy unit's capacity to perform national cancer screening. 14,15 The Accredited Endoscopy Unit Program has recently been updated. 16 Since 1999, gastric cancer endoscopic screening has been provided free of charge to individuals above age 40 every two years based on the high prevalence rate of gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…However the courts did not judge every case as a doctor's performance error. In general, it is known that doctors need to meet a minimum standard of colonoscopy experience to ensure the quality of colonoscopies 26,27 . However, even the most skilled doctors may not avoid colon perforation 28 , and some people are skeptical of requiring for minimal standards of colonoscopy experience 29,30 .…”
Section: Discussionmentioning
confidence: 99%